From Despair to Hope : Hope VI and the New Promise of Public Housing in America's Cities - Engdahl, Lora; Cisneros, Henry (Book collections on Project MUSE., 2009)
"Documents the evolution of HOPE VI, exploring what it accomplished replacing severely distressed public housing with mixed-income communities and where it fell short. Reveals how a program conceived to address a specific problem triggered a revolution in public housing and solidified principles that still guide urban policy today"--Provided by publisher.